Application of 3-D X-ray computed tomography for the in-situ visualization of the SiC crystal growth interface during PVT bulk growth - Neubauer, Georg; Salamon, Michael; Roider, Florian; Uhlmann, Norman; Wellmann, Peter (Materials Science Forum, 2013)
In this paper, we present for the first time an in-situ 3-D reconstruction of the SiC crystal growth interface using X-ray computed tomography (CT). We show that the shape of the growth interface can be determined with high precision at growth temperatures above 2100 °C in a conventional 3 PVT (physical vapor transport) growth system. © (2013) Trans Tech Publications, Switzerlan
Keywords: 3-D X-ray; Computed tomography; CT; PVT; SiC bulk crystal growth